A new class of compact spherical spaces - Dzyadyk, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We describe a class of almost symmetric spherical spaces which is absent in the known classifications made by M. Krämer and I. Mikityuk.